1991
DOI: 10.1002/ddr.430230210
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, neurophysiological, and behavioral effects of Wy‐45,233 and other identified metabolites of the antidepressant venlafaxine

Abstract: Muth, E.A., J.A. Moyer, J.T. Haskins, T.H. Andree, and G.E. M. Husbands:Biochemical, neurophysiological, and behavioral effects of Wy-45,233 and other identified metabolites of the antidepressant venlafaxine. Drug Dev. Res. 23:191-199, 1991. Seven metabolites of venlafaxine, identified in several species, were examined for CNS pharmacological activity in rodents. The 0-desmethyl compound Wy-45,233, which is the major metabolite in man, had the greatest preclinical activity. This metabolite exhibited an anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
105
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(109 citation statements)
references
References 9 publications
2
105
0
2
Order By: Relevance
“…VF is biotransformed in the liver to O-desmethylvenlafaxine (ODV), N-desmethylvenlafaxine (NDV), and N,O-didesmethylvenlafaxine (N,O-DV) (Muth et al 1991). ODV has a receptor affinity profile similar to its parent compound VF, while the latter two metabolites have little if any affinity for the above receptor sites (Muth et al 1991).…”
Section: The Biotransformation Of Venlafaxine (Vf) Into Its Two Majormentioning
confidence: 99%
See 2 more Smart Citations
“…VF is biotransformed in the liver to O-desmethylvenlafaxine (ODV), N-desmethylvenlafaxine (NDV), and N,O-didesmethylvenlafaxine (N,O-DV) (Muth et al 1991). ODV has a receptor affinity profile similar to its parent compound VF, while the latter two metabolites have little if any affinity for the above receptor sites (Muth et al 1991).…”
Section: The Biotransformation Of Venlafaxine (Vf) Into Its Two Majormentioning
confidence: 99%
“…ODV has a receptor affinity profile similar to its parent compound VF, while the latter two metabolites have little if any affinity for the above receptor sites (Muth et al 1991). Previous studies have shown that the biotransformation of VF to ODV is mediated by CYP2D6, and NDV via CYP3A3 ր 4, and possibly a second enzyme (Otton et al 1996).…”
Section: The Biotransformation Of Venlafaxine (Vf) Into Its Two Majormentioning
confidence: 99%
See 1 more Smart Citation
“…CYP2D6 catalyzes the metabolism of VEN to its main metabolite O-desmethylvenlafaxine (ODV) and CYP3A4 is the major enzyme responsible for formation of the minor metabolite N-desmethylvenlafaxine (NDV). Both metabolites are then further metabolized to N,O-didesmethylvenlafaxine (DDV), possibly by CYP2D6 [2,3]. ODV contributes to the overall pharmacological effect of VEN since it exhibits a pharmacological profile similar to that of VEN.…”
Section: Introductionmentioning
confidence: 99%
“…However, the R-enantiomer is a potent inhibitor of both serotonin and noradrenaline reuptake, whereas the S-enantiomer is more selective in inhibiting serotonin reuptake (Holliday et al 1995;Muth et al 1986). Venlafaxine is mainly metabolized by the cytochrome P450 (CYP) enzyme CYP2D6 to its major active metabolite Odesmethylvenlafaxine (Odm-venlafaxine) and to its two minor metabolites, Ndesmethylvenlafaxine (Ndm-venlafaxine) and N,O-didesmethylvenlafaxine (Ddmvenlafaxine) (Muth et al 1991;Muth et al 1986). …”
Section: Introductionmentioning
confidence: 99%